Relationship Between Learning Style With Student Learning Outcomes on Structure and Function of Plants - Elma Nur Hidayati; Ara Hidayat; Ukit Ukit (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2021)
Learning styles can make students learn easily, fun, meaningfully that will improve their learning outcomes. This study aimed to determine the correlation between learning styles and student’s learning outcomes in online learning about structure and function of plant. The correlation test method was used and samples were chosen using simple random sampling, consisting of 68 students in class VIII SMPN 2 Pangkalpinang. The data were collected using interview, questionnaire, documentation methods, and analyzed by Pearson product moment correlation test. The results showed that about 72% students in class VIII SMPN 2 Pangkalpinang tended to have a visual learning style and 75% with completed learning-outcomes. The correlation test indicated that there was no significant relationship between learning styles and their learning outcomes, by evidence and determination value of 0.111 more than 0.05 and 3.8% simultaneously. There is no correlation between learning styles and learning outcomes, presumably because learning styles only contribute 3.8% in which other 96.2% were determined by other factors such as teacher motivation and teaching strategies. However, although there is no correlation, learning styles still contribute to student’s learning success. Therefore, it is necessary to conduct further research related to other factors that may affect student learning outcomes.